Postconcussive syndrome in a high school athlete. Issue 10 (October 2015) - Sasek, Cody A.; Rippee, Michael A.
<x xml:space="preserve">Abstract</x> ABSTRACT: This article describes an adolescent female who had postconcussive symptoms for more than 2 years after sustaining two concussive injuries without complete recovery between them. The case illustrates the significant effect of mild traumatic brain injury and the need for appropriate evaluation and management.